Polymorphisms rs2745557 in PTGS2 and rs2075797 in PTGER2 are associated with the risk of chronic obstructive pulmonary disease development in a Tunisian cohort. (March 2021) - Mani, Salma; Norel, Xavier; Varret, Mathilde; Bchir, Sarra; ben Anes, Amel; Garrouch, Abdelahamid; Tabka, Zouhair; Longrois, Dan; Chahed, Karim
Highlights: Tobacco smoking is the common risk factor of COPD. Gene polymorphisms contribute to inter-individual differences in the response to tobacco smoke in COPD. Potential relationship between COX-2/PGE2 pathway related-gene polymorphisms and COPD risk. Deregulated prostaglandins and cytokines production in plasma of COPD patients may reflect systemic inflammation characterizing COPD. Interaction between pro-inflammatory cytokines and prostaglandins in COPD pathogenesis. Imbalance of oxidative stress makers and lipid mediators in patients with COPD. Abstract: We hypothesized that polymorphisms of genes involved in the prostaglandin pathway could be associated with COPD. In this study we explored the involvement of genetic polymorphisms in PTGS2, PTGER2 and PTGER4 genes in the development and severity of COPD and their effects on plasma concentrations of inflammatory/oxidative stress markers. We identified genotypes of PTGS2, PTGER2 and PTGER4 SNPs in a Tunisian cohort including COPD patients ( n = 138) and control subjects ( n = 216) using PCR-RFLP and PCR TaqMan. Pulmonary function (FEV1 and FVC) were assessed by plethsmography. PGE2, PGD2 and cytokine plasma (IL-6, IL-18, TNF-α, TGF-β) concentrations were measured using ELISA and colorimetric standard methods were used to determine oxidative stress concentrations. Genotype frequencies of rs2745557 in PTGS2 and rs2075797 in PTGER2 were different between COPD cases and controls. There was no correlation between these polymorphisms and lung function parameters. For rs2745557, the A allele frequency was higher in COPD cases than in controls. For rs2075797, carriers of the GG genotype were more frequent in the COPD group than in controls. Only rs2745557 in PTGS2 had an effect on PGD2 and cytokine plasma concentrations. PGD2 was significantly decreased in COPD patients with the GA or AA genotypes. In contrast, IL-18 and NO plasma concentrations were increased in COPD rs2745557 A allele carriers as compared to homozygous GG subjects. Our findings suggest that rs2745557 in PTGS2 and rs2075797 in PTGER2 are associated with COPD development but not with its severity.